Professional Muslim academic reference librarians in the 21st Century / Basri Hassan and Bello Yerima - Hassan, Basri; Bello, Yerima (Faculty of Information Management, 2013)
The paper aims at giving an overview on the best qualities or attribute a qualified academic Muslim librarians should possess for him or her to provide a relevant functional reference services in an academic library environment at the present dispensation. The qualities that Muslim reference librarians should display in their career as information professionals are emphasised. Some of the fundamental qualities include approachability, ability to communicate fluently, determination to do a good job, respect users, show care to users, observing Islamic dress code, willing to promote Islamic resources and collections, subject knowledge, ICT skills and reference interview skills. The paper draws the guideline on the best way to behave, provide appropriate and relevant information, and demonstrate good ethics at the reference desk. This will go a long way in providing quality reference services.